Comportamento do olhar e desempenho esportivo de jogadores não habilidosos durante o lance livre do basquete - Cavalieri, Beatriz Carvalho [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The Quiet Eye (QE) variable measures the duration and location of the last visual fixation before initiating the critical part of movement of a motor task. Studies have shown that QE with longer durations and placed in an important location to the task, indicate better performance of elite players when compared to unskilled. This statement is also true for the free throw of basketball. However, so far it is not known regarding the measurement of this variable in situations relative to the behavior of unskilled players during hit free throw and misses on free throw. The aim of this study was to determine the duration and location of QE in hits and misses free throws from unskilled players. Eight young adults (22.71±1.97 years) with low level of basketball in free throws participated in the study. The gaze behavior during free throw was acquired using the Eye Tracker (ASL, model H6), with a frequency of 60 Hz data acquisition and the movement phases were determined by the video of the movements record by an external camera, being positioned laterally in a sagittal view. The movement phases were: preparation, extension 1, flexion and extension 2, the critical phase for this particular task and QE measurement was at the 'extension 2' of the elbow. For QE analysis, Quiet Eye Solutions software was used to identify the location and duration of QE. Anova one-way with repeated measures were performed with accuracy (hit, miss), with an alpha value of 0.05. The results showed that for the duration mean of the QE there was not significant difference (p = 0.458) between hits throws (898 ± 437ms) and missed throws (808 ± 338ms). The areas determined in the scene to distinguish the fixation locations indicated that during the hits, the location of the QE occurred 30% of the time in the center of the hoop... (Complete abstract electronic access below)

A variável Quiet Eye (QE) mensura a duração e localização da última fixação visual antes de iniciar a parte crítica do movimento de uma ação motora. Estudos têm mostrado que o QE com longa duração e localização importante para a tarefa indicam melhor desempenho dos jogadores de elite quando comparados menos experientes. Esta, afirmação também é verdadeira para o arremesso do lance livre do basquete. Apesar disso, até o momento não se sabe muito sobre a mensuração desta variável em situações que estudem apenas o comportamento dos jogadores não habilidosos durante os lances livres convertidos e lances livres não-convertidos. O objetivo desse estudo foi averiguar a duração e localização do QE em lances livres convertidos e não-convertidos de jogadores não habilidosos. Participaram do estudo, oito adultos jovens (22,71±1,97 anos) com baixo nível de habilidade no lance livre do basquete. O comportamento do olhar durante os arremessos de lance livre foram obtidos através do uso do Eye Tracker (ASL, modelo H6), com frequência de aquisição de dados de 60 Hz e as fases de movimentos foram determinadas pelo registro dos movimentos, feito por uma câmera externa de vídeo, estando posicionada lateralmente em relação ao eixo arremessador-cesta. As fases de movimentos foram: preparação, extensão 1, flexão e extensão 2 sendo que a fase crítica para essa determinada tarefa e mensuração do QE é na 'extensão 2' do cotovelo. Para análise do QE foi utilizado o software Quiet Eye Solutions para identificar o local e duração do QE. Anova one-way com medidas repetidas foi realizada tendo como fator a acurácia (acerto, erro), com valor de alfa de 0,05. Os resultados mostraram que para duração média do QE não houve diferença significativa (p=0,458) entre acertos (898±437ms) e erros (808±338ms)... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Jogadores de basquetebol; Basquetebol; Educação fisica